The Effect of Service Quality and Product Quality on Loyalty Mediated by Customer Satisfaction - Fadilah Fadwa; Zulkifli M. Efendi Sir; Christine Herawati Limbong (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2022)
Service quality and product quality are the most important components in measuring student satisfaction and loyalty, especially for those who are attending education in the field of courses and training. This study aims to determine the effect of service quality and product quality on loyalty which is mediated by customer satisfaction at the Intermedia Computer Training and Training Center Rantauprapat Institute. This study uses quantitative methods. The data analysis technique used is the classical assumption test and this study uses path analysis which will discuss the direct or indirect effects or effects of the intermediary independent variables and the dependent which became the causal hypothesis of the effect on variables with the help of the SPSS version 26 software program for Windows. The results indicate that there is a significant influence between service quality and product quality on satisfaction. But there is no significant effect on the quality of service through student satisfaction on student loyalty. Furthermore, product quality through student satisfaction has a significant and significant effect on student loyalty. And also, the influence has been given to student satisfaction so that there is loyalty given. Due to the results of this study the variable of service quality on loyalty is weak, therefore it is better for the Rantauprapa Intermedia Training Center Course Institute to provide improvements in service quality and be more selective in determining appropriate services and products.